Analisis Kecakapan Hidup (Life Skills) Karateka Remaja: Studi Deskriptif pada Ekstrakurikuler Beladiri Karate di Sekolah Menengah - Shafa Azka Aulia; Agus Gumilar; Salman (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
participating in school karate extracurricular programs based on gender and educational level. The research employed a quantitative approach using a cross-sectional causal-comparative design. The participants consisted of 60 active junior and senior high school karate athletes from BKC Banjar City selected through purposive sampling. Data were collected using the Life Skills Scale for Sport (LSSS), comprising 47 items that assess (1) teamwork, (2) goal setting, (3) social skills, (4) problem-solving, (5) emotional skills, (6) interpersonal communication, (7) leadership, and (8) time management. Data were analyzed using descriptive statistics and Two-Way ANOVA. The results revealed that (1) the overall life skills level of adolescent karate athletes was categorized as very high, with a mean score of 4.85 (SD = 0.36); (2) male karate athletes demonstrated slightly higher life skills scores (M = 4.88; SD = 0.33) than female athletes (M = 4.83; SD = 0.38); (3) senior high school athletes showed higher scores (M = 4.88; SD = 0.34) compared to junior high school athletes (M = 4.80; SD = 0.41); and (4) the Two-Way ANOVA results indicated that gender (p = 0.046), educational level (p = 0.039), and the interaction between gender and educational level (p = 0.047) had significant effects on life skills. These findings suggest that karate extracurricular activities play an important role in fostering students' life skills development, which is influenced by both gender and educational level factors. Keywords: Extracurricular Activities, Gender, Karate, Life Skills, Adolescents